2018
DOI: 10.1186/s13065-018-0478-2
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological activity of hydroxybenzoic acid ester conjugates of phenazine-1-carboxylic acid

Abstract: We prepared 16 novel hydroxybenzoic acid ester conjugates of phenazine-1-carboxylic acid (PCA) and investigated their biological activity. Most of the synthesized conjugates displayed some level of fungicidal activities in vitro against five phytopathogenic fungi. Nine conjugates 5b, 5c, 5d, 5e, 5h, 5i, 5m, 5n and 5o (EC50 between 3.2 μg/mL and 14.1 μg/mL) were more active than PCA (EC50 18.6 μg/mL) against Rhizoctonia solani. Especially conjugate 5c showed the higher fungicidal activity against Rhizoctonia so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The primary fungicidal activities of 10 PCA‐amino acid conjugates were evaluated using an amended agar assay described in our previously published literature . Each test compound was first dissolved within a suitable amount of acetone and diluted with water containing 0.1% Tween 80 to 2 mmol L −1 , and 1 mL of each was then added to 9 mL molten (50 °C) sterile potato dextrose agar (PDA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary fungicidal activities of 10 PCA‐amino acid conjugates were evaluated using an amended agar assay described in our previously published literature . Each test compound was first dissolved within a suitable amount of acetone and diluted with water containing 0.1% Tween 80 to 2 mmol L −1 , and 1 mL of each was then added to 9 mL molten (50 °C) sterile potato dextrose agar (PDA).…”
Section: Methodsmentioning
confidence: 99%
“…The primary fungicidal activities of 10 PCA-amino acid conjugates were evaluated using an amended agar assay described in our previously published literature. 15,17 Each test compound was first dissolved within a suitable amount of acetone and diluted with water containing 0.1% Tween 80 to 2 mmol L −1 , and 1 mL of each was then added to 9 mL molten (50 ∘ C) sterile potato dextrose agar (PDA the PDA culture and PT represented colony diameter of amended agar plates. All statistical analyses were performed using DPS 7.05 software using analysis of variance at P = 0.05.…”
Section: In Vitro Assays Of Fungicidal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] Recent studies have shown that it not only has wide spectrum high efficiency, and low toxicity to human and livestock, but also can be easily degraded in the natural environment and significantly improve crop yield. [20][21][22] At present, it has been registered as 'Shenqinbactin' in China as a biofungicide for the control of rice sheath blight. 23 However, the efficacy of PCA against soil borne diseases is considered low because of the lack of phloem systemicity, which seriously restricts its application to other crops.…”
Section: Introductionmentioning
confidence: 99%
“…are toxins, phenazine‐1‐carboxylate and 2,4‐diacetylphloroglucinol (Haas and Defago, 2005; Ongena and Jacques, 2008). Phenazine‐1‐carboxylate induces the production of the poisonous hydroxyl radical in fungal cells (Zhu et al ., 2018), while 2, 4‐diacetylphloroglucinol causes membrane damage (Haas and Defago, 2005). The synthesis, regulation and applications of these antifungal agents have been covered in recent reviews (Ongena and Jacques, 2008; Raaijmakers et al ., 2010; Pieterse et al ., 2014; Bilal et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%